CLASSROOM INTERACTION ANALYSIS OF ENGLISH CLASS IN SMPN 2 BABALAN - Krisman Sipahutar; Willem Saragih; Indra Hartoyo (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The purpose of this study was to find out the types of interaction, the percentage of teacher talk and student talk and the dominant characteristic of interaction which appeared during teaching-learning process in SMP N 2 Babalan in 2016/2017 academic year. This study used descriptive design. The subjects of this study were three classes. One class of the eighth grade and two classes of the nineth grade. The data were analyzed by using Flanders Interaction Analysis Category System (FIACS). The instruments of collecting data were audio and video recording. The analysis showed that all of the ten types of interaction appeared. The percentages of each types of interaction were: (a) accepting feeling: 0.41%; (b) praising and encouraging: 9.97%; (c) accepting students’ ideas: 0.22%; (d) asking question: 26.26%; (e) lecturing: 4.70%; (f) giving direction: 13.25%; (g) criticizing: 2.21%; (h) tudents talk response: 39.35%; (i) student talk initiation: 1.10%; (j) silence and confusion: 1.93%.   Teacher talk percentages were 60.98% in class 8-1, 51.62% in class 9-2 and 61.15% in class 9-5. And the student talk percentages were 37.31% in class 8-1, 47.29% in class 9-2 and 20.09% in class 9-5. The dominant characteristic of interaction was content cross, which means that the teacher focused on giving questions and giving materials. From the results, the researcher concluded that the teacher was dominant in the classroom during the teaching-learning processes.Keywords: Classroom Interaction , Flanders Interaction Analysis Category System (FIACS). Teacher talk, Student talk.